Availability of Wild Edible Fungi in La Malinche National Park, Mexico. (4th March 2014) - Montoya, A.; Kong, A.; Garibay-Orijel, R.; Méndez-Espinoza, C.; Tulloss, Rodham E.; Estrada-Torres, A.
Abstract : The aim of this paper is to compare edible mushroom availability between the two slopes of La Malinche National Park in central México, and to discuss the possible relation between their availability and traditional use. Eight transects were set up. Samples were collected weekly during the rainy seasons of years 1998–2000. Sixty-one edible mushroom species were collected from a total area of 3200 m 2 (0.32 ha). Over the three-year period, the diversity of mushrooms ranged from 21 to 28 taxa per transect line. Sporocarps were produced at a rate from 2.06 to 6.05 kg/401.51 m 2 . The highest species richness and production values for spatio-temporal frequency were obtained in Southeast slope. Edible mushrooms availability in the Southeast slope showed a strong dominance, driven mainly by Laccaria trichodermophora and Hebeloma mesophaeum . The Southwest slope had more diversified availability in time and space, with the most representative species, being L. trichodermophora . The characteristics of traditional management on each slope determined the differences found.